Hierarchical cubic networks - Ghose, K.; Desai, K.R. (IEEE transactions on parallel and distributed systems, 1995)
We introduce a new interconnection network for large-scale distributed memory multiprocessors called the hierarchical cubic network (HCN). We establish that the number of routing steps needed by several data parallel applications running on a HCN-based system and a hypercube-based system are about identical. Further, hypercube connections can be emulated on the HCN in constant time. Simulation of uniform and localized traffic patterns reveal that the normalized average internode distances in a HCN are better than in a comparable hypercube. Additionally, the HCN also has about three-fourths the diameter of a comparable hypercube, although it uses about half as many links per node-a fact that has positive ramifications on the implementation of HCN-connected systems.< >